Intelligent system - Forbes, David; Wongthongtham, Pornpit; Terblanche, C.; Pakdeetrakulwong, U. (2018)
Ontologies play an important role in enabling knowledge representation, knowledge management, and knowledge sharing. Many applications benefit greatly from making use of ontologies as a means of achieving semantic interoperability among heterogeneous and distributed systems.